Outcome of Carotid Angioplasty With a Novel Open-Cell Carotid Stent System. (May 2014) - Langhoff, Ralf; Mudra, Harald; Waliszewski, Matthias; Reimers, Bernhard; Berge, Jérôme; Setacci, Carlo; Beyssen, Bernard
Background: The choice of carotid stent systems depends primarily on the anatomy of the carotid artery, the lesion morphology, and the patient's risk factors. Design improvements in devices, in terms of crossing profile and the ability to precisely position the stent, may greatly contribute to the procedural success without compromising acute clinical outcomes. Methods and Results: The primary objective of this clinical registry was to evaluate the early safety and efficacy of a novel open-cell carotid stent system in an "all comer" population suitable for carotid artery stenting. The primary end point was the composite of ipsilateral stroke and "all-cause mortality" within 30 days after the procedure. Secondary end points entailed the rates of myocardial infarction and other clinical complications within the first 30 days following the procedure and up to the 6-month follow-up. Unsuccessful placement and/or withdrawal of the delivery system, as well as device-related complications involving the carotid artery and the rate of nonlesion-related embolisms, were evaluated relative to other currently available carotid stents. The 30-day composite death/stroke rate was 2.8% (3 of 106) while the overall stent system performance was similar to commonly used carotid stent systems. Conclusions: The utilized open-cell carotid stent system had favorable lesion crossing and positioning characteristics without compromising the 30-day composite death/stroke rate.